Service-users’ experiences of an early intervention in psychosis service: an interpretative phenomenological analysis - Harris, Katy; Collinson, Christine; das Nair, Roshan (Wiley, 2012)
OBJECTIVES: Previous research regarding Early Intervention in Psychosis (EIP) services has mainly adopted quantitative methodologies, in order to study the effectiveness of EIP services. Research studies that have explored service-users' experiences of EIP services are small in number. This research aimed to explore service-users' experiences of being in contact with an EIP service, its impact of their experience of psychosis and current life situation.